User-Generated Content Sebagai Branding Destinasi Gunungkidul di Youtube Two Mad Explorers - Oktavia Dwi Anggreini; Vani Dias Adiprabowo (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2026)
This study analyzes the role of foreign YouTuber content created by @Two Mad Explorers in constructing tourism promotion discourse for Gunungkidul through a descriptive qualitative approach. The study focuses on the video entitled “Sisi Lain Yogyakarta ?? Gunungkidul”, which presents the authentic experiences of foreign travelers exploring various destinations in Gunungkidul. This research examines both visual and verbal elements in the video, as well as audience responses in the comment section, to understand how User-Generated Content (UGC) contributes to destination image formation. The findings indicate that the video constructs a positive destination representation through visual narratives, personal testimonials, and emotional storytelling. The content highlights local identity, transparent and inclusive destination management, clear location signage, and unique geographical features that enrich the tourism experience. Audience responses in the comment section also demonstrate forms of electronic word-of-mouth (eWOM), indicating the potential to influence audience perceptions and travel interest toward the destination. This study confirms that social media, particularly YouTube, has significant potential as an experience-based tourism promotion medium that can organically strengthen destination branding. Therefore, collaboration between tourism stakeholders and digital creators should be optimized to enhance the competitiveness of local tourism destinations.